2015
DOI: 10.3390/en81212411
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Control Method Using Distributed Generators Based on a Multi-Agent System

Abstract: This paper presents a voltage control method using multiple distributed generators (DGs) based on a multi-agent system framework. The output controller of each DG is represented as a DG agent, and each voltage-monitoring device is represented as a monitoring agent. These agents cooperate to accomplish voltage regulation through a coordinating agent or moderator. The moderator uses the reactive power sensitivities and margins to determine the voltage control contributions of each DG. A fuzzy inference system (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A MAS can be defined as a system comprising multiple intelligent agents that have the abilities of autonomous decision-making and communication with other agents [9,10]. In [11,12], the authors suggested an agent-based algorithm to control the reactive power output of distributed energy resources (DERs) for proper voltage regulation with a few communication requirements. However, they did not consider the coordination between OLTC and DERs.…”
Section: Introductionmentioning
confidence: 99%
“…A MAS can be defined as a system comprising multiple intelligent agents that have the abilities of autonomous decision-making and communication with other agents [9,10]. In [11,12], the authors suggested an agent-based algorithm to control the reactive power output of distributed energy resources (DERs) for proper voltage regulation with a few communication requirements. However, they did not consider the coordination between OLTC and DERs.…”
Section: Introductionmentioning
confidence: 99%
“…Self-healing plays an important role in distribution network [2][3][4][5][6][7][8]. The systems, which have been effectively grounding, protect themselves by switching breakers when grounding faults occur.…”
Section: Introductionmentioning
confidence: 99%
“…Power system stability; (2) Power system reliability; (3) Flexible alternating current transmission systems (FACTS) applied to power systems; (4) Application of optimization methods to power systems; (5) Architectures and models of smart grids; (6) Power market; (7) Control, operation, and planning of distributed generation resources; (8) Smart home with energy management systems; (9) Microgrids and active distribution networks; (10) Virtual power plants and demand response.…”
mentioning
confidence: 99%
“…The transmission system category covers high-voltage direct current (HVDC), FACTS, and thermal standards [5,8,12,21]. The distribution system category covers many topics, such as voltage control, network reconfiguration, microgrids, power quality, smart distribution, and multi-agents [6,10,11,14,20,22]. The end-users category covers demand response, frequency control, and critical peak pricing [7,15,18,19].…”
mentioning
confidence: 99%